IBCA news from the student cultural world
3(1961):no.8 - 4(1962):no.2 is the Spanish ed.: IBCA noticias del mundo cultural estudiantil (see also: ZK 32710). French ed.: IBCA nouvelles du monde culturel étudiant (ZK 32189).